OPPORTUNITIES AND CHALLENGES OF JOURNALISTIC TRANSFORMATION ARTIFICIAL INTELLIGENCE BASED - Supriadin J, Irwan; Anshar, Muhammad (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
Artificial intelligence, which accompanies the advent of Internet technology, has now penetrated all print and electronic media to use new media platforms as a tool to disseminate information to the public. This article explores the potential impact of artificial intelligence (AI) on the media industry by analyzing various aspects of the impact of AI, including news automation, content adaptation, fact-checking, and new ethical challenges that present new opportunities and challenges for journalistic activities. This research is a qualitative study with a descriptive-analytical approach. This approach will allow an in-depth understanding of the impact of artificial intelligence and media transformation on journalistic activities, as well as its opportunities and challenges for the future. AI-based journalism is a system that can independently collect, analyze, and process data through human-created applications, both textual and visual. Although AI can help in some ways to increase the efficiency of journalistic work, the intelligence of a journalist remains irreplaceable in terms of research and investigation